The current state of play relating to Not-for-profit tax concessions in Australia and a glimpse of what may lie ahead for these concessions - Pinto, Dale; Morgan, Annette (School of Business Law, Curtin Business School, Curtin University of Technology, 2011)
There are estimated 600 000 not-for-profit organisations in Australia, contributing around $43 billion to GDP per annum and employing close to 1 million people. They provide a range of assistance within the community and rely heavily on the government and community support to help fund their activities.The paper examines the concessions which are available under the Australian taxation regime for not-for-profit organisations ('NFPOs'). All businesses engaged either directly or indirectly with these organisations should have an understanding of the concessions that are available. As a result of utilising these concessions there can be significant tax savings and the ability to offer attractive salary packages to employees of these organisations. As well as examining the current state of play, this article will also discuss recent announcements by the government in relation to the commercial activities of NFPOs and their ability to access these concessions. In examining the government announcements, the paper will seek to look to the future and take a preliminary view of what really lies ahead for the many not-for-profit tax concessions that is being planned by the government following the 2011 Federal Budget and the subsequent release on 27 May 2011 of its Consultation Paper on this issue.